The impact of S2B2C model on the performance of chain enterprises - ZHAO, Qingyang (Institutional Knowledge at Singapore Management University, 2024)
As the economy is highly developed today, enterprises are studying how to improve channel efficiency, customer loyalty, and supply chain stability along the value chain to ensure their competitive advantages. By observing the development of key chain-operated enterprises in China over the past 20 years, this study proposes to examine the impact of constructing an S2B2C model on corporate performance. A foundational theory has been established, and a theoretical framework has been analyzed. Following a logical order from the abstract to the concrete and from theory to practice, a combination of case studies and empirical analysis is employed to evaluate and analyze the performance of chain enterprises in China. As the external competition environment for enterprises becomes increasingly complex, business model transformation has emerged as a pivotal strategic tool for enterprises to bolster their competitiveness and enhance performance. Business models and their impact on corporate performance have also gained significant traction as a prominent research topic in academia. However, research on business models in China is relatively limited, primarily focusing on the introduction of foreign studies, with most being theoretical in nature and case studies being few and far between. Existing research indicates that the study of business models involves both internal and external factors of enterprises. To conduct an in-depth analysis of the impact of the S2B2C model on corporate performance proposed in this paper, this study encompasses the following work: Firstly, based on a literature review, the S2B2C model is defined. Next, through case studies, in-depth interviews, and questionnaire surveys, I summarize the reasons for enterprises undergoing S2B2C model transformation and the positive impact of this model on corporate performance. After meticulous organization and analysis of the collected data, six dimensions of the antecedent variables influencing the S2B2C model are identified: customer demand, technological change, competition intensity, enterprise resources, organizational structure, and entrepreneurship. Finally, by dissecting relevant concepts and components, a research model investigating the impact of the S2B2C model on corporate performance is constructed and the hypotheses are tested. The main contributions of this study are as follows: 1. A conceptual definition of the S2B2C business model has been proposed, followed by a summary of its positive impact on corporate performance and the antecedent components of this model through case studies. 2. A theoretical model has been developed to encompass the antecedent variables of the S2B2C model, the S2B2C model itself, and its impact on corporate performance, which has been empirically tested.